Deciphering the Genetic Basis of Silkworm Cocoon Colors Provides New Insights into Biological Coloration and Phenotypic Diversification. (31st January 2023) - Lu, Yaru; Luo, Jiangwen; An, Erxia; Lu, Bo; Wei, Yinqiu; Chen, Xiang; Lu, Kunpeng; Liang, Shubo; Hu, Hai; Han, Minjin; He, Songzhen; Shen, Jianghong; et al.
Abstract: The genetic basis of phenotypic variation is a long-standing concern of evolutionary biology. Coloration has proven to be a visual, easily quantifiable, and highly tractable system for genetic analysis and is an ever-evolving focus of biological research. Compared with the homogenized brown-yellow cocoons of wild silkworms, the cocoons of domestic silkworms are spectacularly diverse in color, such as white, green, and yellow-red; this provides an outstanding model for exploring the phenotypic diversification and biological coloration. Herein, the molecular mechanism underlying silkworm green cocoon formation was investigated, which was not fully understood. We demonstrated that five of the seven members of a sugar transporter gene cluster were specifically duplicated in the Bombycidae and evolved new spatial expression patterns predominantly expressed in silk glands, accompanying complementary temporal expression; they synergistically facilitate the uptake of flavonoids, thus determining the green cocoon. Subsequently, polymorphic cocoon coloring landscape involving multiple loci and the evolution of cocoon color from wild to domestic silkworms were analyzed based on the pan-genome sequencing data. It was found that cocoon coloration involved epistatic interaction between loci; all the identified cocoon color-related loci existed in wild silkworms; the genetic segregation, recombination, and variation of these loci shaped the multicolored cocoons of domestic silkworms. This study revealed a new mechanism for flavonoids-based biological coloration that highlights the crucial role of gene duplication followed by functional diversification in acquiring new genetic functions; furthermore, the results in this work provide insight into phenotypic innovation during domestication.